3 '-Deoxyadenosine inhibits pre-adipocyte differentiation and biosynthesis of triacylglycerol in 3T3-L1 cells - Shin, Yong-Kyu; Ye, Michael B.; Kim, Sung-Won; Lee, Soo-Chan; Kim, Il-Woung; Kim, Su-Nam; Yang, Hyun-Ok; Kim, Si-Kwan (ELSEVIER SCIENCE BV, 2014)
This study intended to develop anti-obesity compounds from natural sources. In our screening program for anti-obesity agents, a compound isolated from Cordyceps militaris was found to be a potent inhibitor of the differentiation of 3T3-L1 pre-adipocytes. The active ingredient of C. militaris was isolated from methanol extracts by chromatography, re-crystallized in water, and subsequently identified as 3'-deoxyadenosine, otherwise known as cordycepin. Cordycepin was a potent inhibitor of cellular differentiation and triacylglycerol (TAG) synthesis at a concentration of 32 mu M without any signs of cytotoxicity. However, the inhibitory action was attenuated by supplementation with adenosine. Western blot analysis revealed that cordycepin down-regulated the protein levels of C/EBP alpha, PPAR-gamma, and anti-leptin; these proteins are known to be associated with TAG synthesis. Cordycepin-induced decrease in protein expression was countered by the addition of adenosine. In vitro pharmacokinetic studies demonstrate that 95% of the cordycepin (64 mu M initial concentration) added to the culture medium of 3T3-L1 cells was cleared within 6 h. The metabolic rate of cordycepin in vitro was similar to that of adenosine, suggesting that cordycepin inhibits the differentiation of pre-adipocytes and blocks the synthesis of TAG in 3T3-L1 cells by interfering with adenosine metabolism. (C) 2014 Published by Elsevier Ltd.
Keywords: CORDYCEPS-SINENSIS; SCIENTIFIC REDISCOVERY; PPAR-GAMMA; MILITARIS; OBESITY; PREVALENCE; MEDICINE; RECEPTOR; WEIGHT